New drugs for the treatment of epilepsy: a practical approach. Issue 948 (5th October 2004) - Beyenburg, S; Bauer, J; Reuber, M
Abstract : The availability of new antiepileptic drugs has broadened the spectrum of medical treatment options in epilepsy. The new agents, together with established drugs, offer substantial choice for doctors treating patients with focal or generalised epilepsy. The newer antiepileptic drugs are not necessarily more effective but usually better tolerated than the traditional agents, mainly because of favourable pharmacokinetic profiles and fewer interactions. Because treatment options have increased, drug therapy can now be tailored to the requirements of individual patients. Nevertheless, significant safety and efficacy issues continue to exist and there is a need for the development of even better agents. This review describes the clinical use of the new antiepileptic drugs, but focuses in particular on monotherapy, the treatment of generalised seizures, teratogenicity, and the cognitive side effect profile of the newer compounds.